2017
DOI: 10.1155/2017/7502935
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Thyroid Abnormalities in Thai Patients with Vitiligo

Abstract: Background Vitiligo is an acquired hypopigmentary disorder. The prevalence of vitiligo is 0.1–2% worldwide. Numerous autoimmune diseases are associated with vitiligo, including autoimmune thyroid diseases. The prevalence of thyroid abnormalities is up to 34% in vitiligo patients depending on ethnicities. Objective This study aims to investigate thyroid abnormalities in Thai patients with vitiligo. Methods Medical records of vitiligo patients attending outpatient dermatology clinic at a university-based hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
(34 reference statements)
3
11
1
Order By: Relevance
“…Previous studies have reported presence of hypothyroidism in 15-40% of patients with vitiligo in different regions (1,7,10,16,17). Similar to our findings, Sedighe and Gholamhossein (16) Studies have suggested screening for thyroid abnormalities in these patients with no united guidelines; most of the guidelines have recommend screening in those with familial history of thyroid disease, female gender, longer duration and stressful events (9).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous studies have reported presence of hypothyroidism in 15-40% of patients with vitiligo in different regions (1,7,10,16,17). Similar to our findings, Sedighe and Gholamhossein (16) Studies have suggested screening for thyroid abnormalities in these patients with no united guidelines; most of the guidelines have recommend screening in those with familial history of thyroid disease, female gender, longer duration and stressful events (9).…”
Section: Discussionsupporting
confidence: 87%
“…The disease etiology is complex and multifactorial, including autoimmune, neural, and self-destructive mechanisms as well as genetics, environment, inflammatory, and oxidative stress origin (6)(7)(8)(9). The disease association with other autoimmune diseases, such as systemic lupus erythematosus, scleroderma, alopecia areata, and autoimmune thyroid diseases, has been demonstrated before (1,4,(7)(8)(9)(10). Even recent studies have suggested that thyroid autoimmunity would trigger and affect the depigmentation process of vitiligo (8).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the prevalence of ANA positivity among the vitiligo patients was 35.3%, which was relatively high, compared with other studies 9 . Furthermore, compared to the ANA‐negative group, the ANA positivity was associated with the female gender and positive anti‐thyroglobulin.…”
Section: Discussioncontrasting
confidence: 53%
“…Patients will report itch and ongoing inflammation when lesions newly develop or expand, even if the severity of pruritus does not match that reported in atopic dermatitis . Interestingly, patients with vitiligo are more likely to develop vitiligo and vice versa .…”
Section: Intracellular Metabolismmentioning
confidence: 99%
“…[48] A critical finding may be that lower ATP production caused by mitochondrial dysfunction in vitiligo melanocytes can be compensated for by stabilizing mitochondrial cardiolipin. [49] Patients will report itch and ongoing inflammation when lesions newly develop or expand, [50,51] even if the severity of pruritus does not match that reported in atopic dermatitis. [52] Interestingly, patients with vitiligo are more likely to develop vitiligo and vice versa.…”
Section: Intr Acellul Ar Me Tabolis Mmentioning
confidence: 99%